Million dollar baby - Eastwood, Clint, 1930-; Haggis, Paul.; Ruddy, Albert S., 1934-; Rosenberg, Tom.; Swank, Hilary; Freeman, Morgan; Mackie, Anthony, 1978-; Baruchel, Jay, 1982-; Colter, Mike, 1976-; Eastwood, Kyle.; Rijker, Lucia, 1967-; O'Byrne, Brian F.; et al. (Burbank, CA : Warner Bros. Entertainment : Distributed by Warner Home Video, 2005)
Frankie is a former boxing manager, who initially refuses to train Maggie due to her gender and age. With her talent and his coaching, the spirited young fighter rises through the ranks of women's boxing and the pair form a touching bond in the process.
A male boxing trainer attempts to help a young female boxer achieve her dream of becoming a professional.
disc 1. Movie -- disc 2. Special features.
Based on short stories from the book: Rope burns / by F.X. Toole.
Originally produced as a motion picture in 2004.
Widescreen format (2.35:1).
"Enhanced for widescreen TVs"--Container.
Special feature (disc 1, 2 min.): theatrical trailer.
Special features (disc 2, 57 min., in English with optional French subtitles): "Born to fight" featurette, examining the parallels between the movie & the experiences of real-life boxer Lucia Rijker (19 min.); "The producers : round 15" making-of featurette with Ruddy, Rosenberg & Haggis (13 min.); "James Lipton takes on three", roundtable discussion with Eastwood, Swank & Freeman (25 min.).
Keywords: Toole, F. X., -- 1930- -- Film adaptations; Rijker, Lucia, -- 1967-; Rijker, Lucia, -- 1967-; Toole, F. X., -- 1930-; Boxing trainers -- Drama; Women boxers -- Drama; Boxing for women -- Drama; Boxing for women; Boxing trainers; Women boxers; Feature films -- United States; Drama; Film adaptations; Feature films; Sports films; Fiction films; Feature films; Film adaptations; Video recordings for the hearing impaired; Short films; Documentary films; Nonfiction films